The Management of Children with Chronic Health Problems at School from the Perspective of Parents - María del Pilar Morales Ruíz; Isabel María Fernández-Medina; Antonio Javier Alias-Castillo; María Isabel Ventura-Miranda; María del Mar Jiménez-Lasserrotte; María Dolores Ruíz-Fernández (Nursing Reports)
Background: The prevalence of chronic health problems in childhood, such as food and respiratory allergies, as well as endocrine and skin disorders, has increased globally. Parents and children experience difficulties in managing their illness that reduce their quality of life and increase the presence of negative feelings such as fear or anxiety during school hours. Objectives: The aim of this study was to describe and understand the parents’ experiences of the management of children with chronic health problems during school hours. Methods: A qualitative descriptive study design was used. Semi-structured interviews were conducted with 17 parents (1 male and 16 female) who have children with a chronic health problem between September 2022 and June 2023. The data were analyzed with the help of a qualitative data analysis software. The COREQ checklist was used to develop the study. Results: Two categories and four subcategories emerged from the data analysis: (1) Parents’ Perceptions, with the subcategories 1.1., The School Nurse, and 1.2., Educational Environment; and (2) Chronic Pediatric Health Problems, with the subcategories 2.1., Emotional Impact, and 2.2., Lack of Resources. Conclusions: Children with chronic health problems are unprotected during school hours due to the absence of a school nurse. Parents and teachers have to cope with their care without the necessary knowledge, which makes it difficult to manage children with chronic health problems in the school environment.